The Leadership Role of Pratama Officials in Facing the Salatiga Government's Bureaucracy Simplification Policy - Sabrina Sella Devi; Fuad Mas’ud (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
The implementation of government bureaucratic services in various sectors is the external face of the performance of the government in power, it can reflect how leadership practices are implemented. This study was conducted with the aim of uncovering the processes, obstacles, and problems encountered in the implementation of bureaucratic simplification in Salatiga City Government and the role of high-ranking officials in each regional apparatus in its implementation. This research is a qualitative research using phenomenological study. The data used are primary and secondary data. Primary data was collected through interviews with twelve participants consisting of heads of work units (high-ranking officials) and functional officials resulting from the simplification of the bureaucracy in the relevant work units in Salatiga city government, while secondary data was collected through observation, and documentation on Salatiga city government documents during a certain period. The data analysis technique used was Interpretative Phenomenological Analysis (IPA). Based on the analysis, it is found that bureaucratic simplification still faces many obstacles, especially in the adaptation and technological knowledge of officials. In addition, the simplification of bureaucracy in Salatiga city government raises concerns about career paths coupled with a decrease in employee performance, the head of the field or leader in Salatiga city government plays an important role in dealing with bureaucratic simplification policies to maintain a conducive atmosphere in the organisation and encourage increased employee competence, but the competency improvement program has not been implemented optimally.